Comparative Proteomic and Phosphoproteomic Analyses Reveal Molecular Signatures of Myocardial Infarction and Transverse Aortic Constriction in Aged Mouse Models - Fang Lin; Yue Ding; Xiaoting Liang (Cardiology Research and Practice)
In the elderly population, coronary heart disease (CHD) often coexists with hypertension. However, excessive blood pressure reduction can paradoxically increase the incidence of adverse events. Understanding the molecular mechanisms underlying hypertension and CHD in aged populations is crucial for developing targeted therapies and improving clinical outcomes. In this study, we constructed myocardial infarction (MI) and transverse aortic constriction (TAC) modelsY in aged mice to simulate the disease states of CHD and hypertension, respectively. Using integrated proteomic and phosphoproteomic analyses, we investigated the molecular signatures associated with MI and TAC in these models. Our aim was to identify key molecules involved in these conditions and to understand their unique and shared characteristics. Through our comprehensive proteomic and phosphoproteomic analysis, we identified a total of 1583 proteins and 232 phosphorylated proteins. We observed significant upregulation of heart disease markers such as Myh7, Xirp2, and Acta1, indicating the successful establishment of the MI and TAC models. The overlapped differentially expressed proteins (DEPs) and differentially phosphorylated proteins (DPPs) in MI and TAC were involved in heart failure-related processes including cardiac muscle contraction and hypertrophic cardiomyopathy, further supporting the validity of the models. Among the DEPs, Ppme1 was upregulated in the TAC model but downregulated in the MI model, while Sec31a and Gm56451 displayed the opposite expression patterns. Among the DPPs, Ablim1 and Atp2a2 were found to be significantly upregulated in the TAC model, whereas their expression was markedly reduced in the MI model. In addition, five other DPPs, including REV_Q3TAY5, Cbx3, PITPNB, Eif4b, and A0A1Y7VP73, were elevated in the MI model but decreased in the TAC model. In conclusion, these findings suggest that MI and TAC not only share certain molecular features but also retain their unique characteristics, providing potential biomarkers and therapeutic targets.